Information for Decision Making by Patients With Early-Stage Prostate Cancer: A Comparison Across 9 Countries - (:unkn) unknown (SAGE PUBLICATIONS INC, 2011)
Purpose: To describe decisional roles of patients with early-stage prostate cancer in 9 countries and to compare the information they rated important for decision making (DM). Method: A survey of recently treated patients was conducted in Canada, Italy, England, Germany, Poland, Portugal, Netherlands, Spain, and Turkey. Participants indicated their decisional role in their actual decision and the role they would prefer now. Each participant also rated (essential/desired/no opinion/avoid) the importance of obtaining answers, between diagnosis and treatment decision, to each of 92 questions. For each essential/desired question, participants specified all purposes for that information (to help them: understand/decide/plan/not sure/other). Results: A total of 659 patients participated with country-specific response rates between 58%-77%. Between 83%-96% of each country's participants recalled actually taking an active decisional role and, in most countries, that increased slightly if they were to make the decision today; there were no significant differences among countries. There was a small reliable difference in the mean number of questions rated essential for DM across countries. More striking, however, was the wide variability within each country: no question was rated essential for DM by even 50% of its participants but almost every question was rated essential by some. Conclusions: Almost all participants from each country want to participate in their treatment decisions. Although there are country-specific differences in the amount of information required, wide variation within each country suggests that information that patients feel is essential or desired for DM should be addressed on an individual basis in all countries.
Keywords: early-stage prostate cancer; patient information needs; patient education; NEEDS; MEN; CARE; AID; PREFERENCES; SUPPORT; WANT